2022
DOI: 10.1021/acs.jafc.1c07176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cell Wall Chemistry of Della and Its Mutant Sweet Sorghum Stalks

Abstract: The cell wall compositional (lignin and polysaccharides) variation of two sweet sorghum varieties, Della (D) and its variant REDforGREEN (RG), was evaluated at internodes (IN) and nodes (N) using high-performance liquid chromatography (HPLC), pyrolysis−gas chromatography-mass spectrometry (Py-GCMS), X-ray diffraction (XRD), and two-dimensional (2D) 1 H− 13 C nuclear magnetic resonance (NMR). The stalks were grown in 2018 (D1 and RG1) and 2019 (D2 and RG2) seasons. In RG1, Klason lignin reductions by 16−44 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 85 publications
3
5
0
Order By: Relevance
“…The S/G ratio of the internode rind was determined from Py-GCMS data (Figure 7a). The S/G ratios were 0.29, 0.36, 0.34, and 0.38, respectively for D1, RG1, D2, and RG2, which was consistent with previous work [93]. The S/G ratios of RG1 and RG2 were significantly increased, respectively, by 24.1% and 11.4%.…”
Section: Py-gcms and Dfrc Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The S/G ratio of the internode rind was determined from Py-GCMS data (Figure 7a). The S/G ratios were 0.29, 0.36, 0.34, and 0.38, respectively for D1, RG1, D2, and RG2, which was consistent with previous work [93]. The S/G ratios of RG1 and RG2 were significantly increased, respectively, by 24.1% and 11.4%.…”
Section: Py-gcms and Dfrc Analysissupporting
confidence: 91%
“…The total content of β-O-4-ethers for palm kernel lignin was reported at 2.29 mmol/g [108]. β-O-4 lignin linkages were the main linkages detected by 2D-NMR in sorghum stalks [93]. The data (Table 6) also indicated that 63-71% of β-O-4 were released as G monomer.…”
Section: Py-gcms and Dfrc Analysismentioning
confidence: 88%
“…The charcoal sample's HHV values were in the following order: AA > PA > HM > VP. The charcoal calorific values compare well to a study on the combustion quality analysis of briquettes, which found that all of the materials met the minimum standards for a solid fuel rather than coal 19 . The caloric value reveals the quality of biomass, as its caloric value determines its energy contents 4 .…”
Section: Physico-chemical Characterization Of Charcoalsupporting
confidence: 63%
“…The utilization of biomass materials as source for energy-related applications is typically accompanied by physicochemical characterization since it provides crucial information about the feedstock's physical, chemical, and thermal properties as well as its structural profile 18 . In fact, for predictive purposes, several studies have established functional relationships between the higher heating value (HHV) of biomass and its physicochemical characteristics, namely Volatile matter (VM) or Fixed carbon (FC), ash, carbon (C), Nitrogen (N), and hydrogen (H) 19,20 . An essential quality to qualify a fuel that provides information on fuel breakdown is the combination of elemental analysis, compositional analysis, and calorific value.…”
Section: Physico-chemical Characterization Of Biomassmentioning
confidence: 99%
“…41 Cellulose, hemicellulose and lignin exist as polymers in the plant cell wall, and the linkages between them loosened with the biodegradation of YC49, which released some of the soluble hemicellulose. 42 Meanwhile, sufficient consumption of polysaccharides composed of glucose and arabinose by YC49 and the increase of the content of other components were the main reasons for the decrease in the percentage of glucose and arabinose.…”
Section: Xrd Analysismentioning
confidence: 99%